Case Report:Pregnancy and birth in a mild phenotype of Alström syndrome - Marozio, Luca; Dassie, Francesca; Bertschy, Gianluca; Canuto, Emilie M.; Milan, Gabriella; Cosma, Stefano; Maffei, Pietro; Benedetto, Chiara (Frontiers in Genetics, 2022)
Background: Alström syndrome (AS) is an ultrarare multisystemic progressive disease caused by autosomal recessive variations of the ALMS1 gene (2p13). AS is characterized by double sensory impairment, cardiomyopathy, childhood obesity, extreme insulin resistance, early nonalcoholic fatty liver disease, renal dysfunction, respiratory disease, endocrine and urologic disorders. In female AS patients, hyperandrogenism has been described but fertility issues and conception have not been investigated so far. Case: This case report describes the spontaneous conception, pregnancy, and birth in a 27-year-old woman with AS, characterized by a mild phenotype with late onset of visual impairment, residual perception of light, and hypertension. Before pregnancy, menses were regular with increased levels of dihydrotestosterone and androstanediol glucuronide in the follicular phase, and the ovaries and endometrium were normal during vaginal ultrasound. A thorough clinical follow-up of the maternal and fetal conditions was carried out. A weight gain of 10 kg during pregnancy was recorded, and serial blood and urine tests were all within the normal range, except for mild anemia. The course of pregnancy was uneventful up to 34 weeks of gestation when preeclampsia developed with an abnormally high level of blood pressure and edema in the lower limbs. At 35 weeks + 3 days of gestation, an urgent cesarean section was performed, and a healthy male weighing 1,950 g was born. Histological examination of the placenta showed partial signs of flow obstruction, limited abruption areas, congested fetal vessels and villi, and a small single infarcted area. Conclusion: The present case demonstrates for the first time that conceiving is possible for patients with ALMS. Particular attention should be given to the management of AS systemic comorbidities through the course of pregnancy.